Siswa Moderat: Workshop Pembuatan Konten Edukasi Moderasi Beragama Berbasis Teknologi Bagi Siswa di MA Wihdatul Ulum Gowa - Tahir, Ilyas; Shamad, Ishaq; Nengsi, Ratika; A Natsir, Andi Fadhilah (KHIDMAH: Jurnal Pengabdian Masyarakat, 2026)
The digital literacy skills of students in the madrasah environment still need to be improved to present educational content that reflects the values of religious moderation. This community service program aims to improve the ability of MA Wihdatul Ulum Gowa students in producing educational digital content with the theme of religious moderation. The activity was carried out through several stages, namely preparation, socialization of the concept of religious moderation and digital literacy, technical training in content production, intensive mentoring, to curation and publication of works. The pre-post-test evaluation showed a significant increase in understanding of the values of tawasuth, tasamuh, tawazun, and i'tidal with an average difference of 35%. In addition, participants produce digital content works consisting of short videos, and educational posters, and podcasts published on the school's digital media platform. This program also contributes to increasing students' confidence in digital communication, the formation of moderate attitudes, and the dissemination of peaceful and inclusive religious messages in society. Thus, this PkM activity has proven to be effective in strengthening religious moderation through a digital literacy approach based on content creativity and is recommended to be developed sustainably through the formation of a community of moderation content creators in schools.